Allocation of Expenditures in Elderly Households and the Cost of Widowhood - Daniel Burkhard (Swiss Journal of Economics and Statistics, 2017)
Widowhood and retirement change the economie environment of elderly households. While retirement changes income and expenditure patterns, widowhood fundamentally changes the structure of the household. Besides high non-monetary cost of losing the partner, resources are no longer shared and economies of scale arising from joint consumption are lost. This paper applies a collective household model to expenditure data on elderly households in Switzerland. The findings suggest that 44% of household resources are assigned to wives and both spouses save roughly 27% or, on average, 800 Swiss Francs on monthly expenditures relative to living apart. Estimates of indifference scales indicate that men suffer a financial loss after losing their wife, while widowed women do not.
Keywords: D12; D13; C30; 330; Collective household model; indifference scale; resource shares; economies of scale in consumption; Engel curves; elderly households